A History of the Study of Apocrypha in Early Medieval England - Hawk, Brandon W. (2019)
Literature written in England between about 500 and 1100 CE attests to a wide range of traditions, although it is clear that Christian sources were the most influential. Biblical apocrypha feature prominently across this corpus of literature, as early English authors clearly relied on a range of extra-biblical texts and traditions related to works under the umbrella of what have been called “Old Testament Pseudepigrapha” and “New Testament/Christian Apocrypha." While scholars of pseudepigrapha and apocrypha have long trained their eyes upon literature from the first few centuries of early Judaism and early Christianity, the medieval period has much to offer. This article presents a survey of significant developments and key threads in the history of scholarship on apocrypha in early medieval England. My purpose is not to offer a comprehensive bibliography, but to highlight major studies that have focused on the transmission of specific apocrypha, contributed to knowledge about medieval uses of apocrypha, and shaped the field from the nineteenth century up to the present. Bringing together major publications on the subject presents a striking picture of the state of the field as well as future directions.
Keywords: Anglo-Saxon England; Apocrypha; history of Christianity; Pseudepigrapha